Prolonged fasting followed by refeeding modifies proteome profile and parvalbumin expression in the fast-twitch muscle of pacu (Piaractus mesopotamicus). - Rafaela Nunes da Silva-Gomes; Maria Laura Gabriel Kuniyoshi; Bruno Oliveira da Silva Duran; Bruna Tereza Thomazini Zanella; Paula Paccielli Freire; Tassiana Gutierrez de Paula; Bruno Evaristo de Almeida Fantinatti; Rondinelle Artur Simões Salomão; Robson Francisco Carvalho; Lucilene Delazari Santos; Maeli Dal-Pai-Silva (PLoS ONE, 2019)
Here, we analyzed the fast-twitch muscle of juvenile Piaractus mesopotamicus (pacu) submitted to prolonged fasting (30d) and refeeding (6h, 24h, 48h and 30d). We measured the relative rate of weight and length increase (RRIlength and RRIweight), performed shotgun proteomic analysis and did Western blotting for PVALB after 30d of fasting and 30d of refeeding. We assessed the gene expression of igf-1, mafbx and pvalb after 30d of fasting and after 6h, 24h, 48h and 30d of refeeding. We performed a bioinformatic analysis to predict miRNAs that possibly control parvalbumin expression. After fasting, RRIlength, RRIweight and igf-1 expression decreased, while the mafbx expression increased, which suggest that prolonged fasting caused muscle atrophy. After 6h and 24h of refeeding, mafbx was not changed and igf-1 was downregulated, while after 48h of refeeding mafbx was downregulated and igf-1 was not changed. After 30d of refeeding, RRIlength and RRIweight were increased and igf-1 and mafbx expression were not changed. Proteomic analysis identified 99 proteins after 30d of fasting and 71 proteins after 30d of refeeding, of which 23 and 17, respectively, were differentially expressed. Most of these differentially expressed proteins were related to cytoskeleton, muscle contraction, and metabolism. Among these, parvalbumin (PVALB) was selected for further validation. The analysis showed that pvalb mRNA was downregulated after 6h and 24h of refeeding, but was not changed after 30d of fasting or 48h and 30d of refeeding. The Western blotting confirmed that PVALB protein was downregulated after 30d of fasting and 30d of refeeding. The downregulation of the protein and the unchanged expression of the mRNA after 30d of fasting and 30d of refeeding suggest a post-transcriptional regulation of PVALB. Our miRNA analysis predicted 444 unique miRNAs that may target pvalb. In conclusion, muscle atrophy and partial compensatory growth caused by prolonged fasting followed by refeeding affected the muscle proteome and PVALB expression.